2020
DOI: 10.1101/2020.04.21.049973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two decades of suspect evidence for adaptive DNA-sequence evolution – Less negative selection misconstrued as positive selection

Abstract: Evidence for biological adaptation is often obtained by studying DNA sequence evolution. Since the analyses are affected by both positive and negative selection, studies usually assume constant negative selection in the time span of interest. For this reason, hundreds of studies that conclude adaptive evolution might have reported false signals caused by relaxed negative selection. We test this suspicion two ways. First, we analyze the fluctuation in population size, N, during evolution. For example, the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
3
2
0
Order By: Relevance
“…In agreement with recent findings that positive selection is in general difficult to detect especially in the presence of repeated relaxed purifying selection (Chen et al, 2020), we found weak evidence for positive selection in the golden panchax using both population genetics and phylogenetic methods.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with recent findings that positive selection is in general difficult to detect especially in the presence of repeated relaxed purifying selection (Chen et al, 2020), we found weak evidence for positive selection in the golden panchax using both population genetics and phylogenetic methods.…”
Section: Discussionsupporting
confidence: 92%
“…The relax method relies on fixed differences between species, which probably reflect the selective pressure in a more ancient past. Over a recent time frame, however, population size declined steadily over the past 200,000 generations in most of the golden panchax populations we analysed, probably reflecting the rising sea level and the shrinking island size since the last glacial period (Grant et al, 2012 In agreement with recent findings that positive selection is in general difficult to detect especially in the presence of repeated relaxed purifying selection (Chen et al, 2020), we found weak evidence for positive selection in the golden panchax using both population genetics and phylogenetic methods.…”
Section: Recent Decline Of Population Size Accompanied By Limited Relaxed Selection and Positive Selectionsupporting
confidence: 88%
“…In agreement with recent findings that positive selection is in general difficult to detect especially in the presence of repeated relaxed purifying selection (Chen, et al 2020), we found weak evidence for positive selection in the golden panchax using both population genetics and phylogenetic methods.…”
Section: Long Term Decline Of Population Size Accompanied By Limited supporting
confidence: 92%
“…In Chen et al (2020), the indirect inferences of changes in negative selection through time as a function of Ne changes have been done in several species of primates [55]. Most interesting, by using PSMC, one could take the direct approach to negative selection by calculating Pa/Ps for each time interval.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the current report, we now outline a path forward that is elaborated in the companion study [55]. In taking the new path, we are concerned with measuring the fluctuation in negative selection without addressing the many factors underlying the fluctuation.…”
Section: Discussionmentioning
confidence: 99%